Efficient induction and rapid identification of haploid grains in tetraploid wheat by editing genes TtMTL and pyramiding anthocyanin markers - Chang, Yanan; Tang, Huali; Wang, Surong; Li, Xi; Huang, Peipei; Zhang, Jiahui; Wang, Ke; Yan, Yueming; Ye, Xingguo (Frontiers in Plant Science, 2024)
Doubled haploid (DH) technology provides an effective way to generate homozygous genetic and breeding materials over a short period of time. We produced three types of homozygous TtMTL gene-edited mutants (mtl-a, mtl-b, and mtl-ab) by CRISPR/Cas9 in durum wheat. PCR restriction enzymes and sequencing confirmed that the editing efficiency was up to 53.5%. The seed-setting rates of the three types of mutants ranged from 20% to 60%. Abnormal grain phenotypes of kernel, embryo, and both embryo and endosperm abortions were observed in the progenies of the mutants. The average frequency of embryo-less grains was 25.3%. Chromosome counting, guard cell length, and flow cytometry confirmed that the haploid induction rate was in the range of 3%–21% in the cross- and self-pollinated progenies of the mtl mutants (mtl-a and mtl-ab). Furthermore, we co-transformed two vectors, pCRISPR/Cas9-MTL and pBD68-(ZmR + ZmC1), into durum wheat, to pyramide Ttmtl-edited mutations and embryo-specifically expressed anthocyanin markers, and developed a homozygous durum haploid inducer with purple embryo (DHIPE). Using DHIPE as the male parent to be crossed with the wild-type Kronos, the grains with white embryos were identified as haploid, while the grains with purple embryos were diploid. These findings will promote the breeding of new tetraploid wheat varieties.